Traditional Chinese medicine : scientific basis for its use - Adams, J. D. (James D.); Lien, Eric J., 1937- (RSC drug discovery series., 2013)
Traditional Chinese medicine has a strong scientific basis, but the science of these important preparations is often rarely discussed. Western approaches often simplify traditional Chinese medicine to drug discovery in Chinese plants, however, the majority of traditional Chinese medications use complex mixtures of plant extracts, rather than single purified drugs. The combination of different extracts is based on yin, yang and chi theories, which are often poorly understood in the West. Yin and yang are known to be the balance of agonists and antagonists, whereas chi derives from signalling pr.